2010
DOI: 10.1007/s00428-009-0873-0
|View full text |Cite
|
Sign up to set email alerts
|

A tumor-specific cellular environment at the brain invasion border of adamantinomatous craniopharyngiomas

Abstract: Craniopharyngiomas (CP) are benign epithelial tumors of the sellar region and can be clinicopathologically distinguished into adamantinomatous (adaCP) and papillary (papCP) variants. Both subtypes are classified according to the World Health Organization grade I, but their irregular digitate brain infiltration makes any complete surgical resection difficult to obtain. Herein, we characterized the cellular interface between the tumor and the surrounding brain tissue in 48 CP (41 adaCP and seven papCP) compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 61 publications
5
39
0
Order By: Relevance
“…All xenografts showed a typical bordering zone between tumor tissue and the surrounding brain. This area, marked by a distinct gliosis and appearance of undifferentiated neuroepithelial cells, was similar to that seen in human adaCP (8). Even the growth behavior was comparable between the primary tumor and the xenograft model.…”
Section: Imaging and Histology Revealed Tumor Engraftment In All Tumosupporting
confidence: 73%
“…All xenografts showed a typical bordering zone between tumor tissue and the surrounding brain. This area, marked by a distinct gliosis and appearance of undifferentiated neuroepithelial cells, was similar to that seen in human adaCP (8). Even the growth behavior was comparable between the primary tumor and the xenograft model.…”
Section: Imaging and Histology Revealed Tumor Engraftment In All Tumosupporting
confidence: 73%
“…Unusually, nuclear-cytoplasmic localization of activated b-catenin is found in only a small proportion of tumor cells, either as small cell clusters, which broadly correlate with epithelial whorls, or otherwise dispersed in a minority of cells throughout the tumor (9,11). We have recently described the 3D structure of human ACP using high resolution micro-CT (m-CT) imaging (2), and corroborated the presence of clusters at the leading invasive edge of tissue invasion (8,26).…”
Section: Introductionmentioning
confidence: 73%
“…Karavitaki et al (2005) found after a 10-year follow-up phase up to 40% of patients suffering from obesity. As known from histological specimen resected during surgery, the tumors show finger-like invasion into brain tissue (Burghaus et al, 2010). The surgical attempt to resect these parts will damage the adjacent brain tissue.…”
Section: Discussionmentioning
confidence: 99%